THE RESEARCH TEAM OF THE COV2SOUL.RS PROJECT, REPORTS THE PRELIMINARY RESULTS ON DEPRESSIVENESS IN SERBIA, ON THE OCCASION OF THE WORLD MENTAL HEALTH DAY: Preliminary data on depression in Serbia today - Marić, Nađa; Knežević, Goran; Terzić Supić, Zorica; Mihić, Ljiljana; Pejović-Milovančević, Milica; Lazarević, Ljiljana; Vuković, Olivera; Tošković, Oliver; Todorović, Jovana (Srpski medicinski časopis Lekarske komore, 2021)
Letter to the editor